Preliminary pharmacognostic, physicochemical and phytochemical evaluation of Sansevieria cylindrica leaves (Journal of Pharmaceutical Negative Results, 2022)
Background: Sansevieria cylindrica (S. cylindrica) Bojer ex Hook. (Asparagaceae) is an indoor ornate plant. The plant was conventionally utilized by the local healers during deliberate, and accidental injuries. The pharmacognostic study of this plant with different parameters was very poorly explored. Hence, the present investigation was carried out to explore, and evaluate different characteristics of the plant. Aim: To explore the preliminary pharmacognostic, physicochemical, phytochemical, microscopic, and phytoconstituents potential of S. cylindricaleaves for authentication of the plant. Method: The morphology, and microscopic properties of plant leaves were evaluated. The herbal standardization was then carried out based on physicochemical parameters including ash values, extractive values, and fluorescence analysis. The qualitative evaluation of phytoconstituents was performed using different chemical tests followed by quantitative estimation of important phytochemical, and analytical profiling of extract. Result: The macroscopy has studied for the basic features like colour, size, odor, shape, taste, surface, and fracture of plant leaves. The microscopical study confirms the presence of vessels, vascular bundles, lignified fibers, and calcium oxalate crystals etc. Physicochemical evaluation showed less quantity of inorganic matter present in the plant. Preliminary phytochemical analysis confirms the presence of glycosides, phenolic compounds, tannins, saponins, flavonoids, steroids, and carbohydrates. Instrumental analysis has given an idea about the identification, and confirmation of various phytoconstituents in the extract. Conclusion: The result of the present study can be meaningfully used as a reference for the standardization, and quality control of S. cylindrica and for the authentication, and preparation of monograph of the plant.